Isteriku seorang doktor koleksi kisah suami-suami insan bergelar doktor - Muhamad Nur Farhan Muhamad Fadzil; Muhammad Izzuddin Selamat; Mohammed Rasheedan Ellin; Mohamad Izham Mohd Alias; Zulfadli Zakaria; Mursyidi Mohammad Ir; Abdul Hilmi Mohd Sarnudin; Aiman Rosli; Mohd Fauzi Mohd Bashir (Koleksi tarbiah sentap, 2016)
Himpunan pelbagai kisah suami-suami doktor